Structural analysis of HyFlex EDM instruments. (11th March 2016) - Iacono, F.; Pirani, C.; Generali, L.; Bolelli, G.; Sassatelli, P.; Lusvarghi, L.; Gandolfi, M. G.; Giorgini, L.; Prati, C.
Abstract: Aim: To compare the phase transformation behaviour, the microstructure, the nano‐hardness and the surface chemistry of electro‐discharge machined HyFlex EDM instruments with conventionally manufactured HyFlex CM. Methodology: New and laboratory used HyFlex EDM were examined by X‐ray diffraction (XRD) and differential scanning calorimetry (DSC). Nano‐hardness and modulus of elasticity were also investigated using a maximum load of 20 mN with a minimum of 40 significant indentations for each sample. Raman spectroscopy and field emission‐scanning electron microscope (FE‐SEM) were used to assess the surface chemistry of HyFlex EDM. HyFlex CM were subjected to the same investigations and used as a comparison. Nano‐indentation data were statistically analysed using the Student's t‐test. Results: XRD analysis on HyFlex EDM revealed the presence of martensite and rhombohedral R‐phase, while a mixture of martensite and austenite structure was identified in HyFlex CM. DSC analysis also disclosed higher austenite finish (Af) temperatures for electro‐discharge machining (EDM) instruments. Significant differences in nano‐hardness and modulus of elasticity were found between EDM and CM files ( P < 0.05). FE‐SEM and EDS analyses confirmed that both new EDM and CM files were covered by an oxide layer. Micro‐Raman spectroscopy assessed the presence of rutile‐TiO2 . Conclusions: HyFlex EDM revealed peculiar structural properties, such as increased phase transformation temperatures and hardness. Present results corroborated previous findings and shed light on the enhanced mechanical behaviour of these instruments.